2022
DOI: 10.1101/2022.08.09.22278385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Lifting School Masking Requirements on Incidence of COVID-19 among Staff and Students in Greater-Boston Area School Districts: A Difference-in-Differences Analysis

Abstract: Background. In February 2022, following the rescinding of a Massachusetts statewide school masking mandate, only two cities (Boston and neighboring Chelsea) out of 79 school districts in the greater-Boston area, maintained masking requirements in K-12 schools. This provided an opportunity to examine the impact of removing masking on COVID-19 case rates among students and staff in the public-school setting. Methods. We used difference-in-differences for staggered policy adoption to compare incidence of COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…For example, a study from Boutzoukas et al 6 in the USA found that optional school masking was associated with a 3.6 times higher rate of infection than universal masking districts; however, contact tracing guidance for the regions defines close contacts for testing differently, depending on whether the index case and contacts were masked. A similar bias is present in a recent preprint from Boston whereby the need to test close contacts of COVID-19 cases was exempt if they were wearing masks 7. These are examples of detection of the outcome (COVID-19 cases) being differentially conditioned on the exposure (mask wearing).…”
mentioning
confidence: 82%
“…For example, a study from Boutzoukas et al 6 in the USA found that optional school masking was associated with a 3.6 times higher rate of infection than universal masking districts; however, contact tracing guidance for the regions defines close contacts for testing differently, depending on whether the index case and contacts were masked. A similar bias is present in a recent preprint from Boston whereby the need to test close contacts of COVID-19 cases was exempt if they were wearing masks 7. These are examples of detection of the outcome (COVID-19 cases) being differentially conditioned on the exposure (mask wearing).…”
mentioning
confidence: 82%
“…Such reductions can occur without draconian measures such as lockdowns by using a multipronged approach to slow the spread of COVID-19. Many of these strategies are wellestablished, including improved indoor air ventilation, paid leave to encourage individuals to stay home when infected, improved access to high quality sensitive tests, indoor masking, and robust contact tracing programs (197)(198)(199)(200)(201)(202). Reducing the onward transmission from long-term infections is a crucial part of this strategy as well (150), given the importance of intrahost evolution to the current mode of variant emergence (164,203).…”
Section: Discussionmentioning
confidence: 99%